Jual Beli Air Bersih di Desa Banaran Kecamatan Pulung Kabupaten Ponorogo Perspektif Hukum Positif dan Hukum Islam - Arlinta Prasetian Dewi; Okky Iskandar (Iqtishodia: Jurnal Ekonomi Syariah, 2020)
Water is an important role in human life. The existence of water makes economic activities come alive and develop. This study aims to conduct an in-depth analysis related to the practice of buying and selling clean water in Banaran Village, Pulung District, Ponorogo Regency in the perspective of positive law and Islamic law. This research is qualitative. Data collection techniques using interview and documentation techniques. Data analysis techniques using qualitative data analysis. The conclusion of the study shows that the practice of buying and selling clean water in Sooro hamlet in Banaran village, Pulung subdistrict, Ponorogo regency is not in accordance with positive law and Islamic law